Effect of transferrin glycation induced by high glucose on HK-2 cells in vitro - Ma, Yanqi; Zhou, Qikai; Zhao, Pingping; Lv, Xiaoyu; Gong, Caixia; Gao, Jie; Liu, Jingfang (Frontiers in Endocrinology, 2023)
Background and objective Glycation is a common post-transcriptional modification of proteins. Previous studies have shown that advanced glycation end modified transferrin (AGE-Tf) levels in diabetic rat kidney tissues were increased; however, its role in diabetic nephropathy remains unclear. In this study, differences in glycation degree and Tf sites induced by differing high glucose concentrations in vitro and the effect on total iron binding capacity (TIBC) were observed. Moreover, the effect of AGE-Tf on human renal tubular epithelial cells (HK-2) was investigated. Methods In vitro Tf was incubated with increasing glucose concentrations (0 mM, 5.6 mM, 11.1 mM, 33.3 mM, 100 mM, 500 mM, and 1,000 mM) for AGE-Tf. Differences in AGE-Tf glycation degree and TIBC level were analyzed via colorimetric method. The AGE-Tf glycation sites were identified with LC-MS/MS. HK-2 cells were treated with AGE-Tf prepared with different glucose concentrations (33.3 mM and 500 mM) in vitro. The effects of AGE-Tf on HK-2 cell viability, proliferation, oxidative stress index, and Tf receptor expression levels were then observed. Results With increasing glucose concentrations (100 mM, 500 mM, and 1,000 mM) in vitro, Tf glycation degree was significantly increased. The TIBC levels of AGE-Tf were decreased significantly with increasing glucose concentrations (33.3 mM, 100 mM, 500 mM, and 1,000 mM). Four glycated modification sites in Tf and 17 glycated modification sites were detected in AGE-Tf (500 mM) by LC-MS/MS. The structural types of AGEs were CML, G-H1, FL-1H2O, FL, and MG-H1. No significant differences were found in the survival rate of HK-2 cells among the AGE-Tf (500 mM), AGE-Tf (33.3 mM), and Tf groups (all p > 0.05). The apoptosis rate of HK-2 cells in the AGE-Tf (500 mM) group was significantly higher than that in the AGE-Tf (33.3 mM) group. Additionally, both of them were significantly higher than that in the Tf group (both p < 0.05). The MDA levels of HK-2 cells in the AGE-Tf (500 mM) and AGE-Tf (33.3 mM) groups were higher than that in the Tf group, but not significantly (both p > 0.05). The T-AOC level of HK-2 in the AGE-Tf (500 mM) group was significantly lower than that in the AGE-Tf (33.3 mM) and Tf groups (both p < 0.001). The GSH level of HK-2 cells in the AGE-Tf (500 mM) group was significantly lower than that in the Tf group (p < 0.05). The expression level of TfR in the AGE-Tf (500 mM) group was also significantly lower than that in the Tf group (p < 0.05). Conclusion The degree and sites of Tf glycation were increased in vitro secondary to high-glucose exposure; however, the binding ability of Tf to iron decreased gradually. After HK-2 was stimulated by AGE-Tf in vitro, the apoptosis of cells was increased, antioxidant capacity was decreased, and TfR expression levels were downregulated.